English performance among skilled workers - Lina, Shaari (2011)
This study aims to examine the English language performance towards skilled workers of IKM, Alor Setar. It also determines the association between gender in English performance among the skill workers in IKM and also to determine the relationship between interest in English language and English performance among the skill workers in IKM. The participation for this study are all 2nd Semester students from four different courses in IKM Alor Setar, such as Certificate in Structural Drawing, Certificate in Architectural Drawing, Certificate in Building Construction and Certificate in Furniture Design. The total number of students is 91 students, which 59 are male students and 32 are the female students. Students' interest of English language learning was measured by using the questionnaire designed and modified from the journal taken from Zavodny (2000); Burt (2004); Gurvinder Kaur Gucharan Singh & Sharan Kaur Garib Singh (2008). Lambert (1963) Theory on intrinsic and extrinsic motivation on students' perception and interest in English language, which relates with their technical and vocational needs in technical learning. The questionnaire consists of 16 questions using the Likert Scale and being rank from 'Strongly Agree' to 'Strongly Disagree'. The collected data was analyzed with One Way ANOVA and Spearman correlation test by using the Statistical Package of Social Science (SPSS) version 16.0. The results showed that students' interest in English language differ according to their perception and needs but not to gender. In addition, the results of the study are using the descriptive analysis by looking at the Mean and percentage of students' achievement in 2010 in English language subject. Gender in English performance showed no major differences and both genders can perform well in learning the English language. Meanwhile, in interest of learning the English language, the skill workers were intrinsically and extrinsically motivated. This is due to their strong desire and realization of the importance of the English language towards their working and learning field. The implication for this research, encouragement and exposure especially in English communication should be focus. Since the skill workers involving with business world and dealing with people, therefore, the English language should be design in much interesting and effective ways in the workshop as well as the communication skills. Through these changes, the technical students will move ahead and feel proud of their achievement.